Pengembangan Sistem Konsultasi Online Pada Klinik Kecantikan Adhwa Beauty Care - Agirani, Juanita; Yang, Yang Agita Rindri; Setya Pratama, Muhammad (Manutech : Jurnal Teknologi Manufaktur, 2024)
Adhwa Beauty Care is a beauty clinic in Pangkalpinang that aims to address administrative complexity by developing an Online Consultation Information System using prototype development methods and the CodeIgniter 3 framework. This research aims to enhance the efficiency and accuracy of facial consultation and treatment reservations by reducing delays and potential errors. The system enables directed online consultations, providing appropriate answers and treatments while addressing clinic data management issues. The system's implementation assists Adhwa Beauty Care in improving operational efficiency, preventing miscommunication, and delivering more targeted services. This study contributes to the development of an online consultation system to support modern beauty clinics.